From risk to resource? - Olofsson, Jennie (Teorija in praksa, 2019)
This paper investigates some ways in which risks concerning electronic waste (e-waste) are done and undone in relation to the concept of circular economy. In doing so, it points to the performative character of risk along with the power relations and subsequent processes of normalisation that underlie these processes of doings and undoings. The findings suggest that e-waste is assumed to pose risk when treated outside the EU, while it is largely understood as a resource when treated within the EU or Western countries. Here, difference is created as e-waste is subjected to spatial transfers, in this case (global) trade.
Keywords: elektronski odpadki; Hazardous wastes; International trade; Mednarodna trgovina; Nevarni odpadki; Ravnanje z odpadki; Risk; Tveganje; Waste management